EVALUASI KESESUAIAN TERAPI DAN EFEK SAMPING PENGGUNAAN ANTIHIPERTENSI PADA PASIEN DIABETES MELLITUS TIPE 2 DENGAN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS RUTIN DI RSU PKU MUHAMMADIYAH YOGYAKARTA - , Fef. Rukminingsih ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Antihypertensive selection accuracy determines the achievement of therapy target toward type 2 diabetes mellitus with chronic kidney disease patients who received regular hemodialysis treatment. The use of drugs in a longtime potentially causes side effects and drug interactions as well. Objective: This research is aimed to discover the appropriate therapy and antihypertensive usage side effects on type 2 diabetes mellitus with chronic kidney patients who received regular haemodialysis treatment at RSU PKU Muhammadiyah Yogyakarta during February â April 2011. Method: This research employed prospective observation by evaluating the appropriateness of therapy and monitoring directly the side effects of antihypertensive agent used toward type 2 diabetes mellitus with chronic kidney disease patients who received regular haemodialysis treatment during February â April 2011. Data collected from medical record and interview with patient or their family was analyzed descriptively. Research results and conclusion: For 42 patients having type 2 diabetes mellitus with chronic kidney disease who received regular haemodialysis treatment, it was defined that patient who received appropriate therapy and achieved blood pressure therapy target was none, 4 patients (9.53%) received appropriate therapy yet the blood pressure remained uncontrolled, 2 patients (4.76%) received inappropriate therapy yet achieved controlled blood pressure and 36 patients (85.71%) received inappropriate therapy with remained uncontrolled blood pressure. From 42 patients, it was defined that there were 11 patients (26,20%) were possible and 5 patients (11,90%) were probable suffered from dry cough, 26 patients (61.91%) were possible for suffered from dizziness, 39 patients (92.86%) were possible suffered from headache, 2 patients (4.76%) were potentially suffered from fatigue and 13 patients (30,95%) were possible and 2 patients (4,76%) were probable suffered from drowsiness.